Teaching Science in English through Cognitive Strategies (GIST – Education and Learning Research Journal, 2012)
This study shows the impact and results of implementing three cognitive strategies in science teaching in English.  The three-month study was carried out with 144 second grade students at a public school of Bogota’s Bilingualism program, but only 40 students contributed in the data collection process. Data collected from observations and fieldnotes, surveys, interviews, videotapes, and photographs revealed that the use of the strategies helped children understand not only the content and language, but also the class tasks. Preliminary findings showed that students are the main actors of their learning, and they gain certain autonomy and independence using the cognitive strategies. On the teachers’ side, strategies facilitated classroom management and engagement. The author recommends the constant and gradual implementation of learning strategies not only in science classes, but also in the rest of the content classes to integrate language and content easily.
Keywords: cognitive strategies; science teaching; sheltered instruction; students’ learning and emotions.